2009
DOI: 10.2337/db09-0211
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Fibrosis and Angiogenesis Promoter SPARC/Osteonectin in Human Adipose Tissue by Weight Change, Leptin, Insulin, and Glucose

Abstract: OBJECTIVEMatricellular Secreted Protein, Acidic and Rich in Cysteine (SPARC), originally discovered in bone as osteonectin, is a mediator of collagen deposition and promotes fibrosis. Adipose tissue collagen has recently been found to be linked with metabolic dysregulation. Therefore, we tested the hypothesis that SPARC in human adipose tissue is influenced by glucose metabolism and adipokines.RESEARCH DESIGN AND METHODSSerum and adipose tissue biopsies were obtained from morbidly obese nondiabetic subjects un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
111
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 42 publications
11
111
3
2
Order By: Relevance
“…Recent evidence suggests that SPARC could be a key player in the pathology of obesity and T2DM. The biological mechanisms involving SPARC in the pathogenesis of IR and T2DM remain poorly understood, although potential mechanisms have been postulated, including the interaction of SPARC and macrophage migration inhibitory factor (MMIF) involved in inflammatory processes (2). In this study, we observed that the fasting plasma SPARC levels were significantly higher in subjects with T2DM compared with IGR and control subjects.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Recent evidence suggests that SPARC could be a key player in the pathology of obesity and T2DM. The biological mechanisms involving SPARC in the pathogenesis of IR and T2DM remain poorly understood, although potential mechanisms have been postulated, including the interaction of SPARC and macrophage migration inhibitory factor (MMIF) involved in inflammatory processes (2). In this study, we observed that the fasting plasma SPARC levels were significantly higher in subjects with T2DM compared with IGR and control subjects.…”
Section: Discussionsupporting
confidence: 59%
“…To the best of our knowledge, this is the first study to describe plasma levels of SPARC in patients with different glucose regulatory conditions. Although SPARC levels have been demonstrated to be downregulated by glucose in vitro (2,13,14), other modulators, including insulin and leptin, which have been reported as positive modulators, may also result in the elevation of SPARC levels in diabetic subjects. Adipose tissue is known to be an active and dynamic organ expressing and secreting several cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations